Adult T‐cell leukemia‐lymphoma as a viral disease: Subtypes based on viral aspects. Issue 5 (30th March 2021) - Nosaka, Kisato; Matsuoka, Masao
Abstract: Adult T‐cell leukemia‐lymphoma (ATL) is caused by human T‐cell leukemia virus type 1 (HTLV‐1) infection. Among HTLV‐1 encoded genes, HTLV‐1 bZIP factor ( HBZ ) and tax are critical for the leukemogenesis of ATL. Adult T‐cell leukemia‐lymphoma needs a long latent period before onset, indicating that both viral genes and alterations (genetic and epigenetic) of the host genome play important roles for leukemogenesis. Viral genes influence genetic and epigenetic changes of the host genome, indicating that the virus is of primary importance in leukemogenesis. HBZ is expressed in all ATL cases, whereas Tax expression is heterogeneous among ATL cases. Different patterns of viral gene expression in tumors are also observed for Epstein‐Barr virus. We propose three subtypes of ATL cases based on Tax expression: high, intermittent, and lost expression. HBZ is detected in all ATL cases. Approximately 25% of all ATL cases lost Tax expression at infection of HTLV‐1, indicating that HBZ is the only viral gene responsible for leukemogenesis in addition to genetic and epigenetic changes of the host genes in these ATL cases. The host immune responses to Tax are also implicated in the heterogeneity of ATL. Thus, ATL is a heterogeneous disease in terms of its viral gene expression, which is important for pathogenesis of this intractable lymphomatous neoplasm. Abstract : In this review, we describe the heterogeneity of adult T‐cell leukemia‐lymphoma (ATL) in regard to viral gene expression, and propose three subtypes of ATL. These findings lead to an understanding of pathogenesis by human T‐cell leukemia virus type 1 and new therapeutic strategies for ATL.